Utilization Of Coconut Fiber Waste As Planting Media As A Business Opportunity For The People - Mohamad Bastomi; Nurhidayah; Della Maharane; Makna Nurin Safira (International Journal of Community Service Implementation, 2023)
Kaliasem Hamlet is one of the hamlets in Kalipare Village, Malang Regency that is experiencing problems with the absence of environmentally friendly coconut fiber waste processing facilities, the local community only utilizes coconut fiber for burning media as a substitute for charcoal. This condition results in the accumulation of coir waste around people's homes and farmers' gardens, whereas in fact this waste can be managed sustainably so that it can be reused and can also provide added value economically. Some of the advantages of coconut fiber are that it has ten times higher water absorption capacity than soil, increases oxygen circulation for plant roots, contains nutrients, potassium, phosphorus, nitrogen, calcium, iron, magnesium, manganese, boron, and zinc. The approach method used in this community service is socialization, counseling, training, and evaluation to the community of Kaliasem Hamlet, which involves all housewives of Kaliasem Hamlet. With these methods, it allows the villagers to share, improve and analyze their knowledge about the condition and life of the village, make plans and act. This service activity provides a solution to the partner's problem, namely by training and mentoring farming community groups, besides that the community knows and recognizes the processing of coconut fiber into cocopeat as a hydroponic planting medium. Besides being able to increase income, it can also meet nutritional needs from cultivated organic vegetables and create an environmentally conscious community through waste that can be processed more optimally.